2018
DOI: 10.1038/s41598-018-31782-y
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Chamber Phakic Intraocular Lens Implantation in Eyes with an Anterior Chamber Depth of Less Than 3 mm: A Multicenter Study

Abstract: This study was aimed to assess the clinical outcomes of Visian ICL (hole ICL; STAAR Surgical, Inc.) implantation for the correction of myopic refractive errors in eyes having an anterior chamber depth (ACD) below the current manufacturer’s recommendation (<3.0 mm). We comprised 365 eyes of 201 consecutive patients (mean age ± standard deviation, 35.7 ± 7.5 years) with spherical equivalents of −8.66 ± 3.54 D. We evaluated the safety, efficacy, predictability, stability, intraocular pressure (IOP), endothelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…In another multicenter studies, we recently showed that posterior chamber phakic intraocular lens implantation offered good safety and efficacy outcomes, and yielded predictable and stable results, with no vision-threatening complications 16 18 . Although the degree of myopic correction is different among these studies, both SMILE and phakic intraocular lens implantation may be viable surgical options for the treatment of myopic refractive errors.…”
Section: Discussionmentioning
confidence: 98%
“…In another multicenter studies, we recently showed that posterior chamber phakic intraocular lens implantation offered good safety and efficacy outcomes, and yielded predictable and stable results, with no vision-threatening complications 16 18 . Although the degree of myopic correction is different among these studies, both SMILE and phakic intraocular lens implantation may be viable surgical options for the treatment of myopic refractive errors.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, Kamiya et al implanted an intraocular lens with an anterior chamber depth of less than 3 mm and found that the postoperative corneal endothelial cell loss rate was 0.2 ± 8.7%, confirming the safety of V4c implantation even in the case of a shallow anterior chamber. They also summarized the statistical results from other studies that examined corneal endothelial cell count after ICL implantation and found that the postoperative corneal endothelial cell loss rate was between −1.1% and 8.5% [ 16 ]. In our clinical experiment, the corneal endothelial cell loss rate at 3 months in the two groups was 0.3% and 1.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We selected the appropriate ICL size by referring to the manufacturer’s nomogram based on the horizontal corneal diameter and anterior chamber depth using AS-OCT. We also determined the ICL power using an online calculator system provided by the manufacturer, which was based on a modified vertex formula [ 6 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Detailed surgical procedures have been described previously in our studies [ 6 , 7 ]. In brief, on the day of surgery, dilating and topically anesthetic agents were administered.…”
Section: Methodsmentioning
confidence: 99%